Preparation, characterization and properties of polypropylene/waste tire dust (PP/WTD) - Mohamad Awang (Pulau Pinang: Universiti Sains Malaysia, 2014)
Thermoplastics and waste rubber from scrap tires were mixed to prepare polypropylene/waste tire dust (PPIWTD) blends. All blends were prepared in an internal mixer at a temperature of 180°C, a rotor speed of 50 rpm and a mixing period between 9 and 13 min. Characterization was done to determine the properties of the blends and to investigate the effects of WTD size, application of dynamic vulcanization and co-agents, addition of other polymeric materials and a 6-month exposure to natural weathering on the mechanical properties, morphology, swelling resistance and thermal properties of the blends.